Leisure-Time Physical Activity in adults with Cerebral Palsy. Issue 4 (October 2015) - Usuba, Koyo; Oddson, Bruce; Gauthier, Alain; Young, Nancy L.
Abstract: Background: Cerebral Palsy (CP) is becoming more prevalent in the adult population, but there is limited information available regarding their Leisure-Time Physical Activity (LTPA). Objective: To investigate the self-reported frequency and LTPA participation patterns in adults with CP, compared to the Canadian general population (CGP). Methods: This was a cross-sectional, follow-up-survey of a cohort of 145 persons with CP. The primary outcome was the level of participation in LTPA. Questions were also posed about the motivations and self-reported barriers to LTPA participation. The survey results were compared to CGP estimates from the Canadian Community Health Survey (CCHS). Results: Fifty-four participants completed the survey, and 90% reported participation in at least one LTPA per week. On average, they reported participating in LTPA 7.3 ± 5.7 times/week. They also reported participating in an average of 4.1 ± 2.4 different types of LTPA. Walking, home-exercise, and swimming were the most frequently reported as a primary LTPA in the CP sample. These finding were comparable to those from the CGP. However, adults with CP were more likely to participate in home-exercise than the CGP ( p < 0.05). More than 40% reported that the purpose of their LTPA was fitness or body maintenance and 56% indicated an interest in starting new activities. Various barriers were also reported. Conclusions: Adults with CP frequently participated in LTPA. However, the majority of them are not achieving recommended daily physical activity levels. Also their LTPA habitually focuses on rehabilitative exercises and the diversity of LTPA is limited by several barriers.